Etrinabdione (VCE-004.8), a B55α activator, promotes angiogenesis and arteriogenesis in critical limb ischemia - García-Martín, Adela; Prados, María E.; Lastres-Cubillo, Isabel; Ponce-Diaz, Francisco J.; Cerero, Laura; Garrido-Rodriguez, Martin; Navarrete, Carmen; Pineda, Rafael; Rodríguez, Ana B.; Muñoz, Ignacio; Moya, Javier; Medeot, Antonella; et al. (Journal of translational medicine, 2024)
Vasculogenic therapies explored for the treatment of peripheral artery disease (PAD) have encountered minimal success in clinical trials. Addressing this, B55α, an isoform of protein phosphatase 2A (PP2A), emerges as pivotal in vessel remodeling through activation of hypoxia-inducible factor 1α (HIF-1α). This study delves into the pharmacological profile of VCE-004.8 (Etrinabdione) and evaluates its efficacy in a preclinical model of critical limb ischemia, with a focus on its potential as a PP2A/B55α activator to induce angiogenesis and arteriogenesis.